When the earth was bare - Judith, Witters (Cengage Learning Australia Melbourne, 1994)
When the Earth Was Bare is a thought-provoking children's book that explores the themes of environmental awareness and conservation. The story depicts a time when the earth was stripped of its natural beauty, showcasing the impact of human actions on the planet. Through engaging illustrations and a compelling narrative, the book encourages young readers to reflect on the importance of protecting nature and the environment. It promotes a message of hope and responsibility, inspiring children to take action and nurture the earth for future generations.